PENERAPAN DATA MINING DENGAN MENGGUNAKAN ALGORITMA C4.5 UNTUK MENGKLASIFIKASIKAN PEREKRUTAN KARYAWAN DI SMK NEGERI 1 NGULING - Endang widia Astuti (STMIK YADIKA BANGIL, 2016)
ABSTRACT : In this study, the authors sought to mine the data an Educational Institution to determine the classification of the recruitment of employees at the school. Existing data were analyzed using a decision tree approach (decision tree) ie the algorithm C4.5. With this algorithm can know the data of candidates which are grouped into classes that qualify prospective employees and data which are grouped into classes do not qualify. The pattern then can be used to determine which job candidates who meet the criteria to be included in the agency, so that the principal can take a decision to accept or reject the prospective employee.Keyword: algorithm C4.5, the classification of employee recruitment, Data Mining